Originally Posted by

**princess_anna57** Solve:

2x + 4 = 4

3x - y = 1

Please double check that you did not make a typo here.

2x + 4 = 4

2x = 4 - 4

2x = 0

x = 0

We now know x = 0

3x - y = 1

3(0) - y = 1

y = -1

Thus:

x = 0

y = -1

Solve:

x - 2y = 7

2x + y = 4

x - 2y = 7

x = 7 + 2y (Set this value for x into the second equation)

2(7 + 2y) + y = 4

14 + 4y + y = 4

5y = -10

y = -2

Now we have a value for y. (y = -2)

Set this value into the first equation.

x -2(-2) = 7

x + 4 = 7

x = 3

Please give step by step instructions. Thank you.